2009
DOI: 10.1104/pp.109.140491
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of Fatty Acids during Natural Senescence of Arabidopsis, Brachypodium, and Switchgrass and in Arabidopsis β-Oxidation Mutants      

Abstract: During leaf senescence, macromolecule breakdown occurs and nutrients are translocated to support growth of new vegetative tissues, seeds, or other storage organs. In this study, we determined the fatty acid levels and profiles in Arabidopsis (Arabidopsis thaliana), Brachypodium distachyon, and switchgrass (Panicum virgatum) leaves during natural senescence. In young leaves, fatty acids represent 4% to 5% of dry weight and approximately 10% of the chemical energy content of the leaf tissues. In all three specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
78
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(87 citation statements)
references
References 52 publications
8
78
0
1
Order By: Relevance
“…TAG was separated from total lipids by thinlayer chromatography (TLC), transmethylated, and quantified by gas chromatography of fatty acid methyl esters (Xu et al, 2005). The data showed that TAG levels are extremely low (around 0.02% of dry weight) in all three wild-type tissues, consistent with previous studies (Yang and Ohlrogge, 2009). However, in the stems and roots of sdp1-5, substantially more TAG accumulated, while the effect was much less pronounced in leaves ( Fig.…”
Section: Disruption Of Sdp1 Leads To Tag Accumulation In Vegetative Tsupporting
confidence: 88%
See 3 more Smart Citations
“…TAG was separated from total lipids by thinlayer chromatography (TLC), transmethylated, and quantified by gas chromatography of fatty acid methyl esters (Xu et al, 2005). The data showed that TAG levels are extremely low (around 0.02% of dry weight) in all three wild-type tissues, consistent with previous studies (Yang and Ohlrogge, 2009). However, in the stems and roots of sdp1-5, substantially more TAG accumulated, while the effect was much less pronounced in leaves ( Fig.…”
Section: Disruption Of Sdp1 Leads To Tag Accumulation In Vegetative Tsupporting
confidence: 88%
“…In this study, we show that disruption of the TAG lipase SDP1 (Eastmond, 2006) leads to an accumulation of oil in vegetative tissues of Arabidopsis, suggesting that TAG turnover occurs in these tissues despite their very low steady-state TAG content (Yang and Ohlrogge, 2009). Although we show that SDP1 is expressed (and the protein is present) in all tissues of a rosette plant, the accumulation of TAG is far more pronounced in heterotrophic tissues (i.e.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Therefore, in order to consider the evidence of specific roles for metabolites in senescence, a more precise analysis of metabolite levels in different tissues and cell types during the process of senescence is required. Although, to date, a number of targeted metabolite profiles, particularly those focused on lipids as seed storage compounds (Yang and Ohlrogge, 2009;Seltmann et al, 2010) and sugars, amino acids, and nutrient ions (Masclaux et al, 2000;Quirino et al, 2001;Stessman et al, 2002;Diaz et al, 2005;Masclaux-Daubresse et al, 2005, 2007Pourtau et al, 2006;Wingler et al, 2006Wingler et al, , 2012, have been generated from maturing and senescing tissues, a broad overview of metabolic changes during senescence, including the interactions between various metabolic pathways, is still lacking. Therefore, we performed a metabolomics study to obtain comprehensive metabolite profiles, including primary and secondary metabolites and lipids, over the course of developmental senescence in rosette leaves before and after bolting and siliques of Arabidopsis in order to investigate the metabolic response and spatiotemporal distribution of metabolites during senescence at the whole-plant level and within single leaves.…”
mentioning
confidence: 99%